Vaccine Distribution and the EU Recovery and Resilience Facility - Corrado Macchiarelli; Renato Giacon (London School of Economics and Political Science (LSE), European Institute, 2022)
In this article, we discuss the interaction between the Covid-19 vaccine rollout in EU member states and the effective use of grants and soft loans from the EU pandemic recovery fund. With some of the national spending plans for the Recovery Fund still awaiting initial submission (Bulgaria), others pending the Commission's endorsement (Poland, Hungary) or formal Council's approval (Romania, Estonia), and various other national plans in their implementation stage, the next challenge for policymakers will be to ensure that the initial and subsequent tranches of EU funds are released as economies reopen. We claim that special attention ought to be paid to Central and Eastern Europe, where some countries are lagging in their vaccine rollout and/or the preparation for their use of the EU recovery funds. This is likely to be an important test for EU institutions in determining the stability and coherence of the European project as a whole.
Keywords: 330; Vaccination; Covid-19; EU